2017
DOI: 10.1089/brain.2016.0440
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation Targeting Primary Motor Versus Dorsolateral Prefrontal Cortices: Proof-of-Concept Study Investigating Functional Connectivity of Thalamocortical Networks Specific to Sensory-Affective Information Processing

Abstract: The pain matrix is comprised of an extensive network of brain structures involved in sensory and/or affective information processing. The thalamus is a key structure constituting the pain matrix. The thalamus serves as a relay center receiving information from multiple ascending pathways and relating information to and from multiple cortical areas. However, it is unknown how thalamocortical networks specific to sensory-affective information processing are functionally integrated. Here, in a proof-of-concept st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 91 publications
3
42
0
Order By: Relevance
“…However, a small number of TDCS-fMRI studies applying TDCS to the primary motor cortex (M1) or dorsolateral prefrontal cortices (dlPFC) have shown effects distant from the site of stimulation (58,28,29). Additionally, a study comparing M1 and left dorsolateral prefrontal cortex TDCS, found that M1 TDCS modulated connectivity of sensorimotor networks, whilst TDCS to the DLPFC additionally modulated affective networks (30). However, the remote effects of TDCS and its interaction with task have not been systematically investigated for networks involved in cognitive control.…”
Section: Discussionmentioning
confidence: 99%
“…However, a small number of TDCS-fMRI studies applying TDCS to the primary motor cortex (M1) or dorsolateral prefrontal cortices (dlPFC) have shown effects distant from the site of stimulation (58,28,29). Additionally, a study comparing M1 and left dorsolateral prefrontal cortex TDCS, found that M1 TDCS modulated connectivity of sensorimotor networks, whilst TDCS to the DLPFC additionally modulated affective networks (30). However, the remote effects of TDCS and its interaction with task have not been systematically investigated for networks involved in cognitive control.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of tDCS-fMRI studies applying tDCS to the primary motor cortex (M1) or dorsolateral prefrontal cortices (dlPFC) have shown effects distant from the site of stimulation (Antal et al, 2011;Park et al, 2013;Peña-Gómez et al, 2012;Polania et al, 2012;Sehm et al, 2013;Stagg & Johansen-berg, 2013). In addition, a study comparing M1 and left dorsolateral prefrontal cortex tDCS found that M1 tDCS modulated connectivity of sensorimotor networks, while tDCS to the DLPFC additionally modulated effective networks (Sankarasubramanian et al, 2017). A previous study stimulating the left IFG found that anodal and cathodal left IFG stimulation differentially modulates brain activation during a verbal frequency task, though this was assessed with functional near infrared spectroscopy so did not assess changes in a distributed network (Ehlis, Haeussinger, Gastel, Fallgatter, & Plewnia, 2016).…”
Section: Stimulation Of the Right Inferior Frontal Gyrus Modulates mentioning
confidence: 99%
“…Increased functional connectivity (FC) was found both in regions proximal to the electrode [30, 34, 38] and in distal regions belonging to the sensorimotor network [31, 36, 39]. Similarly, studies using graph theory, an approach taking into account network topology and synchronization between brain hubs [64], suggested a network-specific enhancement of connectivity following atDCS [32, 33, 35, 37].…”
Section: Local and Distal Connectivity Effects Of Nibsmentioning
confidence: 99%
“…These preliminary results suggest that atDCS over DLPFC and parietal cortex may be effective in modulating specific neural networks relying over these cortical hubs, the FPN and the DMN, respectively. Nevertheless, connectivity changes were also observed in other neural networks: frontal stimulation affected FC within the DMN [43, 47], the language network [44], and subcortical nuclei [36, 46]. Moreover, frontal stimulation resulted in interactions between FPN and DMN FC [47].…”
Section: Local and Distal Connectivity Effects Of Nibsmentioning
confidence: 99%